2015
DOI: 10.1007/s00520-015-2768-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of admission to hospice on pain intensity and type of pain therapies administered

Abstract: Mean ± SD pain NRS values of the entire group were 2.58 ± 2.61 on day 1 and 1.40 ± 1.72 on day 7 (P = 0.002). Restricting the analysis to patients with moderate to severe pain at the time of hospice admission, results were even more significant. In fact, mean ± SD pain NRS was 5.51 ± 1.24 for patients with pain ≥4 at admission and 1.76 ± 1.91 for the same patients after 7 days (P < 0.001). A significant increase in the number of patients receiving morphine was observed from day 1 to day 7 (24 to 41, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…After admission there was a clear improvement of physical and psychological symptoms, as it often occurs in acute or home care settings [ 22 , 23 ], probably as a result of a comprehensive assessment and team experience in symptom control. In a retrospective study, admission to hospice led to a significant reduction of pain intensity, particularly in patients with moderate to severe pain [ 24 ]. It is likely that hospice policies are largely different among countries and even in the same country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After admission there was a clear improvement of physical and psychological symptoms, as it often occurs in acute or home care settings [ 22 , 23 ], probably as a result of a comprehensive assessment and team experience in symptom control. In a retrospective study, admission to hospice led to a significant reduction of pain intensity, particularly in patients with moderate to severe pain [ 24 ]. It is likely that hospice policies are largely different among countries and even in the same country.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, admission to a hospice led to a significant reduction in reported pain intensity for the patients. This decrease in pain was accompanied by a significant increase in the use of morphine, especially via parenteral routes, but not by a higher mean equivalent daily dose of oral morphine per patient [ 24 ]. Thus, hospice care provides an appropriate drug selection for symptom control in comparison with hospital non-specialized care.…”
Section: Discussionmentioning
confidence: 99%
“…Progress in symptom control, hospice, and palliative care belies this depiction of care at the end of life. [59][60][61][62][63][64][65][66][67] Moreover, progress in medical ethics has made it routine for patients to refuse lifesustaining therapies such as ventilators, dialysis, feeding tubes, and cardiopulmonary resuscitation that they judge to be more burdensome than beneficial, and then to be supported in dying. Acceptance of the principle of double effect makes it possible for patients to consent to be treated with sufficient doses of medication to control their symptoms even at the risk of unconsciousness or hastened death.…”
Section: Approaching Deathmentioning
confidence: 99%